Efektifitas Fungi Mikoriza Arbuskular pada Bibit Kelapa Sawit yang Ditanam pada Media Steril dan Tidak Steril - Maria Viva Rini; Novalim Purlasyanko (Jurnal Agroekoteknologi, 2023)
Generally, arbuscular mycorrhizal fungi (AMF) experiment is conducted utilizing sterilized soil. However, the sterilization method would be complicated or impossible to implement in the field application. Therefore, this research aims to investigate whether applying two species of AMF onto oil palm seedling growth planted in non-sterilized soil is still effective. The experiment consists of five treatments, including sterilized media without AMF (T1), sterilized media + FMA Entrophospora sp. (T2), non-sterilized media + FMA Entrophospora sp. (T3), sterilized media + FMA Glomus sp. (T4), and non-sterilized media + FMA Entrophospora sp. (T5). Each of the treatments was repeated four times. The data obtained was tested using analysis of variance and proceeded to the least significant difference test on level alfa 5%. The oil palm seedling was sown in pre-nursery for two months and in the main nursery for three months (the treatment was applied during the transplanting from pre-nursery to the main nursery). The results showed that Entrophospora sp. and Glomus sp. showed a significant result in improving oil palm seedlings’ growth under sterilized and non-sterilized soil with a high root colonization category (>50%). Therefore, both AMF applications are suitable for oil palm plantation fields.